Paper-based composite film

By introducing lignin-covered TiO2 ultraviolet shielding layer, PLA/PBAT gradient barrier layer and Ag@ZIF-8 antibacterial layer into the paper-based composite film, combined with Ar/O2 plasma treatment and ultraviolet radiation technology, the shortcomings of traditional paper-based composite films in terms of barrier, antibacteriality and interface strength are solved, and multiple protection and environmentally friendly effects are achieved.

CN120575448APending Publication Date: 2025-09-02AMCO TECH R&D CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510615184.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-14
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

The existing paper-based composite films have shortcomings in barrier properties, antibacterial properties, degradability and interface strength, which are difficult to meet multiple protection needs, and have sanitary risks and environmental unfriendly problems.

Method used

The composite structure of the ultraviolet shielding layer coated with TiO2, the PLA/PBAT alternating microlayer gradient barrier layer, the antibacterial layer loaded with Ag@ZIF-8 nanoparticles and the PPC/PBS blended heat sealing layer was used to synthesize Ag@ZIF-8 nanoparticles and multi-channel coextrusion dies to prepare microlayer structures, Ar/O2 plasma treatment and ultraviolet radiation, etc., to achieve close bonding of each layer.

Benefits of technology

It achieves efficient ultraviolet shielding, multiple barriers, long-acting antibacterial and high interface strength, improves the comprehensive performance of the composite membrane and reduces environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120575448A_ABST
    Figure CN120575448A_ABST
Patent Text Reader

Abstract

The invention discloses a paper-based composite film, which adopts a four-layer structural design, and the outer layer is an ultraviolet shielding layer formed by coating TiO2 with lignin; the transition layer is composed of 32-64 PLA / PBAT alternating microlayers, and the multiple alternating transition layers form a zigzag gas barrier path; ag-coated ZIF-8 nanoparticles are loaded on the paper base layer, so that long-acting antibiosis is realized by slowly releasing silver ions; and the inner layer adopts a PPC / PBS blend to support the heat sealing layer with adjustable heat sealing strength. According to the preparation process, a gradient micro-layer structure is constructed through a multi-runner co-extrusion die head and a layer multiplier, silver ions are loaded to ZIF-8 through an ultrasonic-vacuum impregnation process, the hydroxyl density of the surface of the paper base layer is improved through plasma treatment, good interlayer strength is achieved, ester bond crosslinking is induced in a pre-irradiation mode, and the product is prepared. The paper-based composite film has ultraviolet shielding, gradient blocking, slow-release antibacterial and controllable heat sealing performance, the interface bonding strength of a traditional paper-based composite film is greatly improved, all components are biodegradable, and the paper-based composite film is suitable for packaging of food, medicine and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of bio-based composite materials, and in particular relates to a composite film, and more particularly to a paper-based composite film and a preparation method thereof. Background Art

[0002] Paper-based composite film is a multi-layer functional material composed of paper and other materials. It combines the advantages of paper and other materials, using paper as the support layer and a resin composite material on the surface to achieve technical benefits such as barrier properties, moisture and oxygen insulation, heat resistance, and improved mechanical strength. Using paper as the support layer makes the paper base biodegradable or recyclable, reducing plastic usage while facilitating printing of designs and text on the paper surface. Combining the stiffness of paper with the flexibility of plastic, it is widely used as a backing material for milk cartons, fast food packaging, and aluminum-plastic blisters.

[0003] However, traditional composite films typically only offer a single barrier property, such as oxygen or water vapor, making them difficult to meet multi-faceted protection requirements. While using a built-in barrier layer like aluminum foil can partially address these issues, the aluminum foil itself compromises the recyclability or biodegradability of the paper-based composite film, necessitating secondary processing for recycling.

[0004] Secondly, paper-based composite films used for medical antimicrobial applications typically incorporate antimicrobial ingredients directly into the paper layer, composite layer, or adhesive. This can lead to the migration of antimicrobial ingredients, resulting in loss of activity and poor antimicrobial durability. Furthermore, there are technical issues with the low interfacial bonding strength between the plastic film and the paper substrate, leading to easy delamination. Summary of the Invention

[0005] The purpose of the present invention is to overcome the shortcomings of the existing technology and provide a paper-based composite film that has barrier properties, antibacterial properties, degradability and high interfacial strength, so as to solve the problems of the composite film shown in the existing technology that it has some functions but some functions are compromised, has high sanitary risks and is environmentally unfriendly.

[0006] To achieve the above objectives, the present invention provides the following technical solutions: A paper-based composite film, comprising: The outer layer comprises a UV shielding layer of lignin-coated TiO2, specifically a film layer made of functional particles of lignin-coated TiO2 as a dispersed phase mixed into a continuous phase of a matrix resin; the matrix resin here can be selected from polyethylene, polypropylene, polyethylene terephthalate, polyamide, etc.; The transition layer is a gradient barrier layer composed of alternating microlayers of polylactic acid (PLA) and polybutylene terephthalate adipate (PBAT). The two materials are extruded into films, stacked, folded in half, and then hot-pressed. This process is repeated to achieve the alternating microlayer structure. A paper base layer, an antibacterial layer loaded with Ag@ZIF-8 nanoparticles, specifically a structure in which the nanoparticles formed by Ag@ZIF-8 are loaded onto the surface of a substrate paper, and the paper includes but is not limited to unbleached kraft paper, pure wood pulp filter paper, bamboo pulp composite paper, sulfate paper, etc.; The inner layer comprises a heat seal layer of a blend of polypropylene carbonate (PPC) and polybutylene succinate (PBS).

[0007] Furthermore, the gradient barrier layer comprises 32-64 alternating microlayers, the thickness of a single layer is 0.5-2 μm, the mass ratio of PLA to PBAT is (3:2)-(4:1), the structure of the alternating microlayers is a cyclic structure in which PLA or PBAT is alternately arranged with another material, and a single layer refers to a film layer formed by one of the two materials.

[0008] Furthermore, the loading of the Ag@ZIF-8 nanoparticles was 1-5% of the paper weight in the substrate, the average Ag@ZIF-8 particle size was 50-100 nm, and the ZIF-8 pore size was 0.8-1.2 nm. As a further illustration, within a certain diameter range of ±5 nm, at least 80% of the Ag@ZIF-8 particles were found to be within this particle size range.

[0009] Furthermore, the mass ratio of polypropylene carbonate to polybutylene succinate in the heat-sealing inner layer is (2:3)-(3:2), and a plasticizer is added in an amount of 2-10% of the total weight of the resin matrix composed of the two polymers, and the plasticizer is preferably a citrate ester.

[0010] Furthermore, the mass ratio of lignin to TiO2 in the ultraviolet shielding outer layer is 1-3:1, and the TiO2 crystal form is a mixed crystal structure of anatase and rutile. Here, the TiO2 mixed crystal structure is used to synergistically enhance the ultraviolet shielding effect.

[0011] The present invention further discloses a method for preparing a paper-based composite film having at least one of the above technical features, comprising the following steps: S1: Ag@ZIF-8 nanoparticles were synthesized by solvothermal method and loaded into the fiber pores of paper substrate; S2: A multi-channel co-extrusion die was used to prepare a PLA / PBAT alternating microlayer structure with 32-64 layers and an extrusion temperature of 160-190°C. S3: Ar / O2 plasma treatment is performed on the paper substrate surface to induce interfacial chemical reaction; S4: Integrate the layers into one by hot pressing, wherein the pressure of the hot pressing is 0.8-1.5 MPa and the time of the hot pressing is 5-15 seconds.

[0012] Further, In S1, the nanoparticles are loaded using an ultrasonic-vacuum impregnation synergistic process with an ultrasonic frequency of 40 kHz and a vacuum degree of -0.08 to -0.1 MPa.

[0013] In S2, the PLA / PBAT melt is passed through a layer multiplier to prepare the alternating microlayer structure, with a layer thickness variation coefficient of less than 5% and an interface diffusion layer thickness of less than 50 nm.

[0014] In S3, the power of the plasma treatment is 150-250W, and the treatment time is 20-60s, so that the hydroxyl density on the surface of the paper base is increased to 8-12 / nm 2 .

[0015] Furthermore, the composite film is pre-irradiated under ultraviolet light with a wavelength of 365 nm for 30-90 seconds to induce an interfacial ester bond cross-linking reaction, thereby promoting the bonding effect between the layers and improving the interfacial bonding strength.

[0016] The advantages and beneficial effects of the present invention are: The present invention is prepared by sequentially stacking an outer layer, a transition layer, a paper base layer and a heat-sealing layer. The outer layer uses lignin to coat TiO2 to achieve ultraviolet absorption function; PLA / PBAT alternating microlayers construct a tortuous diffusion path to achieve a gradient barrier function; Ag@ZIF-8 nanoparticles are loaded on the paper base layer to slowly release Ag through the pore size screening effect. + The heat seal layer uses a PPC / PBS blend system. By changing the blend ratio of the two, the heat seal strength can be adjusted to meet the different needs of high sealing of food packaging or easy tearing of medical consumables.

[0017] The outer layer of the present invention adopts a mixed crystal structure of lignin coated TiO2 through phenolic hydroxyl groups and Ti 4+ Coordination bonding inhibits photocatalytic activity, greatly improves ultraviolet absorption rate, and has less performance degradation in ultraviolet aging experiments, which is significantly better than existing paper-based composite films.

[0018] The present invention further provides a method for preparing the above-mentioned paper-based composite film. By treating the surface of the paper base layer with Ar / O2 plasma, the hydroxyl density is increased, which significantly increases the interfacial chemical bonding sites; subsequent ultraviolet pre-irradiation induces an ester bond cross-linking reaction, which increases the interlayer bonding strength by more than 30%, avoiding the problems caused by interfacial stratification of traditional paper-based composite films. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the structure of the composite membrane shown in the present invention; Figure 2 It is a production process flow chart of the composite membrane shown in the present invention; In the picture: 1-outer layer, 2-transition layer, 3-paper base layer, 4-inner layer. DETAILED DESCRIPTION

[0020] The present invention provides a paper-based composite film comprising an outer layer 1, a transition layer 2, a paper base layer 3, and an inner layer 4, which are sequentially stacked and joined together through a hot pressing process. The outer resin matrix is ​​loaded with lignin-TiO2. The lignin forms a Ti-OC chemical bond with the TiO2 surface via phenolic hydroxyl groups, capturing photogenerated electron-hole pairs. The conjugated aromatic structure of the lignin and the UV shielding properties of the TiO2 create a synergistic effect.

[0021] As an explanation for this mechanism, lignin contains conjugated aromatic structures, and the π-π transitions produced by its electrons absorb UV light in the 280-400 nm range. TiO2 absorbs UV light through its band gap (anatase 3.2 eV, corresponding to 385 nm; rutile 3.0 eV, corresponding to 413 nm), and its mixed crystal structure broadens the absorption spectrum. The efficient light absorption of anatase combined with the high stability of rutile overcomes the narrow UV shielding range of a single crystal form. It is important to note that the mass ratio of lignin to TiO2 should be controlled. Excessive lignin will cause TiO2 to agglomerate and affect its dispersion, while too little lignin will not adequately coat the TiO2, inhibiting its photocatalytic activity in competing UV absorption.

[0022] The transition layer utilizes alternating microlayers, with PLA's high crystallinity (>40%) forming a dense barrier backbone. The flexible segments of PBAT fill PLA's intercrystalline defects, creating a more tortuous path for oxygen or water vapor transmission. The temperature gradient between the two resins during extrusion creates a dynamic crosslinking effect, enhancing the cross-sectional shear strength between them. In the transition layer, the PLA / PBAT mass ratio is selected from (3:2) to (4:1). Barrier properties begin to degrade when the PBAT content exceeds 33%, while PLA content exceeding 80% is prone to brittle fracture.

[0023] The relationship between the transmission path length L of oxygen and water vapor and the number of layers n is L=n×d×sinθ, where θ is the angle between the diffusion path and the two adjacent membrane surfaces. Alternating layers make θ approach 90°, thereby significantly extending the diffusion path.

[0024] It is worth noting that when PLA / PBAT melt is co-extruded, the layer multiplier should maintain the thickness of the interface diffusion layer less than 50nm. DSC can be used to measure Tg shift less than 1% to verify this. Maintaining the thickness of this diffusion layer can reduce the local stress concentration caused by molecular chain entanglement. Although local damage of 5% of the film layer bonding area in the layer multiplier is acceptable.

[0025] The main reason for choosing citrate plasticizers is their biodegradability. Furthermore, the similar polarity of the ester and hydroxyl groups in citric acid is also considered. The Flory-Huggins interaction parameter, χ, is less than 0.5, indicating that citric acid is highly compatible with PPC / PBS, which is beneficial for reducing or minimizing scrap rates during the production of alternating microlayers during the use of the layer multiplier. Specifically, citrate esters can lower the glass transition temperature of PPC / PBS blends by approximately 10°C, maintaining the blend's homogeneous structure while avoiding the phase separation that can be caused by traditional plasticizers. They weaken the interchain hydrogen bonds between PPC / PBS, lowering the melting temperature (Tm) by approximately 10-15°C and improving the melt flow index, facilitating multilayer coextrusion. Citrate esters weaken interchain hydrogen bonds because their molecular weight is higher than that of traditional small-molecule plasticizers, such as DOP, and they compete with PPC / PBS for hydrogen bonds.

[0026] In addition, the carboxyl groups of citrate can bind to the Ag released from Ag@ZIF-8 through chelation. + Formation of complexes, extension of Ag + Sustained release time.

[0027] In the paper base, silver ions are loaded onto the ZIF-8 structure. ZIF-8 is a zeolite imidazolate framework material with a certain topological structure. 2+ Coordinated with 2-methylimidazole to form a tetrahedral unit, the pore size can be precisely controlled within the range of 0.8-2.2nm by changing the synthesis conditions (such as solvent ratio, reaction time). The pore size of ZIF-8 can selectively block molecular-level organic pollutants and achieve a sustained release effect of silver ions. Specifically, after silver ions are loaded into the ZIF-8 structural unit, Ag + This is achieved by forming Ag-N coordination bonds with the unsaturated Zn-N sites in ZIF-8.

[0028] As a further illustration, the sustained release of Ag by nano-ZIF-8 + It combines with the thiol group of bacteria to inactivate the protein and achieve antibacterial effect. At the same time, the ROS (active free radicals) generated by the excitation of TiO2 can also enhance the bactericidal effect. + The release rate conforms to the Higuchi model.

[0029] ZIF-8, CAS: 59061-53-9, can be purchased from any manufacturer or prepared in the laboratory. Preparation methods include, but are not limited to, co-precipitation, hydrothermal, and chemical deposition methods.

[0030] The present invention further provides a method for preparing the above-mentioned paper-based composite film, which uses ultrasound to generate instantaneous pressure to enhance the penetration of ethanol solution and Ag@ZIF into the paper substrate, and combines with a certain range of vacuum to form CO-Zn coordination bonds between ZIF-8 particles and cellulose hydroxyl groups, thereby achieving the anchoring effect of Ag@ZIF-8 on the surface of the paper substrate.

[0031] As a preferred embodiment, Ar / O2 plasma treatment of the paper substrate produces ·O and ·OH active particles, thereby increasing the density of hydroxyl groups (including carboxyhydroxyl groups) on the surface of the paper substrate. Optionally, ultraviolet irradiation is combined with the formation of ester bonds between the terminal hydroxyl groups of PLA and the carboxyl groups of the paper substrate, thereby significantly improving the interlayer bonding strength of the composite film shown in the present invention.

[0032] As a further illustration, 365 nm UV light excites the terminal hydroxyl groups (-OH) of PLA and the carboxyl groups (-COOH) of paper to undergo an esterification reaction: PLA-OH+Paper-COOH→PLA-O-CO-Paper+H2O The aforementioned reaction, measured by DMA as a decrease in the peak tan delta, confirmed an approximately 30% increase in crosslink density between the PLA and the paper substrate. Plasma treatment combined with UV crosslinking increased interlayer bond strength by 50% compared to traditional adhesive methods, eliminating the risk of delamination.

[0033] The following embodiments are further described in conjunction with the accompanying drawings and examples. The following embodiments are only used to more clearly illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention.

[0034] Example 1 A paper-based composite film, comprising: Outer layer: lignin coated TiO2 mass ratio 2:1, anatase / rutile crystal ratio 7:3, film thickness 15μm, outer layer resin is PET, the total mass of lignin and TiO2 is 2% of PET; Transition layer: 32 layers of PLA / PBAT alternating microlayers, single layer thickness 1.5μm, PLA:PBAT=3:2 (mass ratio); Paper base: weight 80g / m 2 Unbleached kraft paper, the Ag@ZIF-8 loading was 2% of the paper substrate weight, and the average pore size of ZIF-8 was 0.9 nm.

[0035] Inner layer: PPC:PBS = 1:1 (mass ratio) resin matrix, to which acetyl tributyl citrate is added at 5% of the total weight of PPC and PBS, with a film thickness of 20 μm.

[0036] The preparation process of the paper-based composite film is as follows: Step 1: 0.1M silver nitrate and 0.4M 2-methylimidazole were solvent-thermally reacted in ethylene glycol at 120°C for 6 hours, and nanoparticles with a particle size of 70 nm were obtained after centrifugation; the paper substrate was placed in a vacuum drying oven for dehydration for 2 hours, and then the paper substrate was immersed in an ethanol solution, and Ag@ZIF-8 nanoparticles with a mass% of the ethanol solution were added to the ethanol solution. At 40kHz and a vacuum degree of -0.09MPa, 1.0% of the paper weight of Ag@ZIF-8 nanoparticles were loaded onto the paper substrate.

[0037] Step 2: Use a 4-layer co-extrusion die to alternately place PLA and PBAT from top to bottom, where PLA is extruded at 175°C and PBAT is extruded at 185°C, and fold three times through a layer multiplier to reach 32 layers.

[0038] Step 3: Using an Ar / O2 mixed gas with a volume ratio of 4:1, the paper substrate loaded with Ag@ZIF-8 nanoparticles was treated at a power of 200 W for 40 seconds to increase the hydroxyl density on the paper substrate surface to 10 / nm 2 .

[0039] Step 4: Place the outer layer, transition layer, paper base layer and inner layer on a hot press in sequence, and hot press at a pressure of 1.0 MPa and 110°C for 10 seconds.

[0040] Example 2 A paper-based composite film, comprising: Outer layer: lignin coated TiO2 mass ratio 3:1, anatase and rutile crystal ratio 6:4, film thickness 10μm; base resin is PP, the total mass of lignin and TiO2 accounts for 3% of PP resin; Transition layer: PLA and PBAT are alternately stacked in 64 layers, with a single layer thickness of 0.5 μm and a PLA:PBAT mass ratio of 4:1.

[0041] Paper base: bamboo pulp composite paper with a gram weight of 60g / m², Ag@ZIF-8 loading of 1%, ZIF-8 pore size of 1.2nm, and particle size of 50nm.

[0042] Inner layer: The mass ratio of PPC to PBS is 3:2, 8% triethyl citrate plasticizer is added, and the film thickness is 20 μm.

[0043] The preparation process of the paper-based composite film is as follows: Step 1: Dissolve 0.1M silver nitrate and 0.4M 2-methylimidazole in ethylene glycol, react at 140°C for 8 hours, and centrifuge to obtain Ag@ZIF-8. Then, immerse a paper substrate in an ethanol solution containing 1 wt% nanoparticles using 40kHz ultrasound, a vacuum of -0.1 MPa, and an immersion time of 30 minutes. Ag@ZIF-8 nanoparticles are loaded onto the paper substrate at a concentration of 3% by weight of the paper.

[0044] Step 2: Use a 4-layer co-extrusion die to alternately place PLA and PBAT from top to bottom, where PLA is extruded at 170°C and PBAT is extruded at 190°C, and folded 4 times by a layer multiplier to reach 64 layers.

[0045] Step 3: Using an Ar / O2 mixed gas with a volume ratio of 4:1, the paper substrate loaded with Ag@ZIF-8 nanoparticles was treated at a power of 250 W for 20 seconds to increase the hydroxyl density on the surface of the paper substrate to 8 / nm2.

[0046] Step 4: After the paper substrate is dried, it is irradiated with 365 nm ultraviolet light for 90 seconds.

[0047] Step 5: Place the outer layer, transition layer, paper base layer and inner layer on a hot press in sequence, and hot press at a pressure of 1.5 MPa and 120°C for 5 seconds.

[0048] Example 3 A paper-based composite film, which differs from Example 1 in that: Outer layer: lignin coated TiO2 mass ratio 3:1, anatase and rutile crystal ratio 6:4, film thickness 10μm; matrix resin is polyethylene, the total mass of lignin and TiO2 accounts for 3% of the matrix resin; Transition layer: PLA and PBAT are alternately stacked in 48 layers, with a single layer thickness of 1.2 μm and a PLA:PBAT mass ratio of 3.5:1.

[0049] Paper substrate: Ag@ZIF-8 loading 1%, ZIF-8 pore size 1.2 nm, particle size 50 nm.

[0050] The preparation process of the paper-based composite film differs from that of Example 1 in that: Step 1: Dissolve 0.2M silver nitrate and 0.8M 2-methylimidazole in DMF, react at 150°C for 12 hours, and centrifuge to obtain Ag@ZIF-8. Then, immerse the paper substrate in an ethanol solution containing 2 wt% nanoparticles using 40kHz ultrasound, a vacuum of -0.1 MPa, and an immersion time of 30 minutes. Ag@ZIF-8 nanoparticles are loaded onto the paper substrate at a concentration of 5% by weight of the paper.

[0051] Step 2: Use a 6-layer co-extrusion die to alternately place PLA and PBAT from top to bottom, and fold it three times using a layer multiplier to reach 48 layers.

[0052] Step 3: Using an Ar / O2 mixed gas with a volume ratio of 4:1, the paper substrate loaded with Ag@ZIF-8 nanoparticles was treated at a power of 200 W for 40 seconds to increase the hydroxyl density on the paper substrate surface to 10 / nm 2 .

[0053] Step 4: After the paper substrate is dried, it is irradiated with 365 nm ultraviolet light for 30 seconds.

[0054] Example 4 A paper-based composite film, which differs from Example 2 in that: Inner layer: The mass ratio of PPC to PBS is 2:3, 10% acetyl trioctyl citrate is added, and the film thickness is 25 μm.

[0055] The preparation process of the paper-based composite film differs from that of Example 2 in that: Step 4: After the paper substrate is dried, it is irradiated with 365 nm ultraviolet light for 60 seconds.

[0056] Step 5: Place the outer layer, transition layer, paper base layer and inner layer on a hot press in sequence, and hot press at a pressure of 0.8 MPa and 105°C for 15 seconds.

[0057] Example 5 A paper-based composite film, which differs from Example 4 in that: Outer layer: lignin and TiO2 mass ratio is 1:1, anatase: rutile = 5:5; the matrix resin is polyamide (PA6).

[0058] The preparation process of the paper-based composite film differs from that of Example 4 in that: Step 4: After the paper substrate is dried, it is irradiated with 365 nm ultraviolet light for 30 seconds.

[0059] Step 5: Place the outer layer, transition layer, paper base layer and inner layer on a hot press in sequence, and hot-roll them at a pressure of 1.5 MPa and 120°C for 20 seconds.

[0060] The above embodiments were subjected to performance tests, and the test standards and test results are shown in Table 1.

[0061] The interlayer strength test was conducted using the T-peel method according to ASTM D1876. The UV absorbance was tested using a QUV weathering instrument at a wavelength of 365 nm using ASTM D4329. The antibacterial rate was tested using the absorption method in ISO 20743. The Ag@ZIF-8-loaded paper substrate was cut into 5 × 5 cm² specimens and sterilized with UV light for 30 minutes. Then, 1 mL of a bacterial suspension with a concentration of 1 × 10 5 CFU / mL, agar medium was added and covered with sterile polyethylene film to prevent evaporation. The cells were incubated at 37°C and relative humidity ≥90% for 30 days. Oxygen transmission rate was determined using the differential pressure method according to ASTM D3985, and water vapor transmission rate was determined using the cup method according to ASTM E96 at 25°C and relative humidity of 90%.

[0062] Table 1: Test items Interlaminar strength, N / 15mm UV absorption rate, % Antibacterial rate, % <![CDATA[Oxygen transmission rate, cm 3 / (m 2 ·24h·0.1MPa)]]> <![CDATA[Water vapor transmission rate, g / (m 2 ·24h)]]> Example 1 >15.5 95 99.9 ≤3 ≤5.2 Example 2 >19.2 98 99.5 ≤5 ≤3.5 Example 3 >18.8 96 98.7 ≤2.5 ≤5.4 Example 4 >22.3 93 98.1 ≤4 ≤6.2 Example 5 >21.2 92 97.2 ≤4.5 ≤8.1 The technical results shown in Table 1 demonstrate that the lignin-coated TiO2 technology employed in this invention achieves high UV absorption, reducing the risk of UV degradation of the substrate while also providing excellent UV protection. The PLA / PBAT gradient barrier layer employed in this invention achieves relatively good oxygen and water vapor barrier properties, while the Ag@ZIF-8-loaded structure exhibits excellent long-lasting antibacterial properties.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A paper-based composite film, characterized in that: It includes the following layers stacked in sequence: an outer layer, a UV shielding layer containing lignin-coated TiO2; a transition layer, a gradient barrier layer composed of alternating microlayers of polylactic acid and polybutylene terephthalate-adipate; a paper-based layer, an antibacterial layer loaded with Ag@ZIF-8 nanoparticles; and an inner layer, a heat-sealing layer containing a blend of polypropylene carbonate and polybutylene succinate.

2. The composite membrane according to claim 1, characterized in that The gradient barrier layer comprises 32-64 alternating microlayers, a single layer thickness of 0.5-2 μm, and a mass ratio of PLA to PBAT of (3:2)-(4:1).

3. The composite membrane according to claim 1, characterized in that The loading amount of the Ag@ZIF-8 nanoparticles is 1-5% of the weight of the paper in the paper base, the average particle size of the Ag@ZIF-8 nanoparticles is 50-100 nm, and the pore size of ZIF-8 in the Ag@ZIF-8 is 0.8-1.2 nm.

4. The composite membrane according to claim 1, characterized in that The heat-sealing inner layer comprises polypropylene carbonate and polybutylene succinate in a mass ratio of (2:3) to (3:2), and 2-10 wt % of a plasticizer is added.

5. The composite membrane according to any one of claims 1 to 4, characterized in that The mass ratio of lignin to TiO2 in the outer layer is 1-3:1, and the TiO2 crystal form is a mixed crystal structure of anatase and rutile.

6. A method for preparing the composite membrane according to claim 1, comprising the following steps: S1: Synthesis of Ag@ZIF-8 nanoparticles and loading them into the fiber pores of the paper substrate; S2: A multi-channel co-extrusion die was used to prepare a PLA / PBAT alternating microlayer structure with 32-64 layers and an extrusion temperature of 160-190°C. S3: Ar / O2 plasma treatment is performed on the paper substrate surface to induce interfacial chemical reaction; S4: Integrate the layers by hot pressing at a pressure of 0.8-1.5 MPa for 5-15 seconds.

7. The preparation method according to claim 6, characterized in that The nanoparticles in S1 were loaded using an ultrasonic-vacuum impregnation process with an ultrasonic frequency of 40 kHz and a vacuum degree of -0.08 to -0.1 MPa.

8. The preparation method according to claim 6, characterized in that The PLA / PBAT melt in S2 is processed through a layer multiplier to prepare the alternating microlayer structure, with a layer thickness variation coefficient of <5% and an interface diffusion layer thickness of <50 nm.

9. The preparation method according to claim 6, characterized in that In step S3, the plasma treatment power is 150-250W and the treatment time is 20-60s, so that the hydroxyl density on the surface of the paper base is increased to 8-12 / nm 2 .

10. The preparation method according to any one of claims 6 to 9, characterized in that: The composite film was pre-irradiated with ultraviolet light at a wavelength of 365 nm for 30-90 seconds to induce an interfacial ester bond cross-linking reaction.

Citation Information

Cited By

  • Method for ultrasonic-assisted continuous controllable synthesis of one-dimensional core-shell structure nano material

    CN121928034A

  • A method for ultrasonic-assisted continuous controllable synthesis of one-dimensional core-shell structure nanomaterials

    CN121928034B